Multilingual Education Policy and LOTE Teacher Development: Focusing on China's LOTE Programs in Higher Education - Wenjun Yu; Hao Xu (MDPI AG, 2023)
This article, drawing on recent research on Language Other than English (LOTE) programs in China's universities, examines the impact of multilingual education policy on the professional development of LOTE teachers. We argue for the mediating roles of LOTE programs as they carry the influence of education policy on teacher development. In other words, LOTE programs may influence the way in which education policy impacts teacher development. Specifically, LOTE programs seem to play three mediating roles: (1) How education policy is perceived and understood by the program designer or/and coordinator impacts how LOTE teachers who engage in the program are influenced, (2) how educational resources are allocated to teachers teaching in the LOTE program impacts teachers' professional development, (3) how teachers actually position themselves in the LOTE program as opposed to their identities positioned by education policy and the university administration impacts their professional development. In a word, the influence of multilingual education policy on the professional development of LOTE teachers may be mediated by such meso- and micro-level factors as administration, resource, and identity work.